1980
DOI: 10.1111/j.1699-0463.1980.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO STIMULATION OF BLOOD LYMPHOCYTES FROM MYCOPLASMA PNEUMONIAE INFECTED PATIENTS WITH PNEUMONIA AND WITH DISORDERS OF THE CENTRAL NERVOUS SYSTEM

Abstract: stimulation of blood lymphocytes from Mycoplasrna pneurnoniae infected patients with pneumonia and with disorders of the central nervous system. Acta path. microbiol. scand. Sect. C, 88: 61-65, 1980. In 23 patients with Mycoplasma pneurnoniae (MP) infection ( I 3 with pneumonia and 10 with an acute febrile, non-bacterial disorder of the central nervous system (CNS)) and in 26 healthy control persons, thymidine incorporation of blood lymphocytes stimulated in vitro by killed MP was studied. The lymphocyte re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In addition, blood lymphocytes from patients in acute phase of Mycoplasma pneumoniae infection have been shown to have a decreased response to purified protein derivatives in vitro [26]. Hence, it has been suggested that Mycoplasma pneumoniae infection causes transient depression of cell-mediated immunity [26]. It appears possible that the depressed cell-mediated immunity during the acute Mycoplasma pneumoniae infection predisposed our patient to the development of Chrombobacterium violaceum infection which manifested as skin abscess.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, blood lymphocytes from patients in acute phase of Mycoplasma pneumoniae infection have been shown to have a decreased response to purified protein derivatives in vitro [26]. Hence, it has been suggested that Mycoplasma pneumoniae infection causes transient depression of cell-mediated immunity [26]. It appears possible that the depressed cell-mediated immunity during the acute Mycoplasma pneumoniae infection predisposed our patient to the development of Chrombobacterium violaceum infection which manifested as skin abscess.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, blood lymphocytes from patients in acute phase of Mycoplasma pneumoniae infection have been shown to have a decreased response to purified protein derivatives in vitro [26]. Hence, it has been suggested that Mycoplasma pneumoniae infection causes transient depression of cell-mediated immunity [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antigen preparation. M.pneumoniae was cultured, washed and sonicated as previously described (15). This non-viable preparation had a protein concentration of 0.5 g/litre.…”
Section: Methodsmentioning
confidence: 99%
“…2) Mycoplasma pneumoniae was cultured, washed and sonicated as previously described (8). The preparation was employed in 7 concentrations with 3-fold dilution steps; 20 pl were added to the cultures.…”
Section: )mentioning
confidence: 99%